Penerapan Target Costing Dalam Upaya Pengurangan Biaya Produksi Untuk Peningkatan Laba Kotor - Johan, Elmer Tamara; ., Muanas (Jurnal Ilmiah Akuntansi Kesatuan, 2014)
PT. Mercedes-Benz Indonesia is a manufacturing company engaged in the automotive field. The company produces cars with various kinds dan types, such as : C-Class sedan type vehicle, and koupe Estate, E-Class sedan type vehicle, the M-Class Sports Utility Veihicle vehicle type (SUV), the S-Class sedan type vehicle. The purpose of this study was to determine the pricing of the selling C-Class and the cost of production C-Class, as well as know Class C gross profit using target costing. Results of research that has been done, it can be seen that the method used by the company is not efficient. But after using the method of target costing, profit desired by the company can be achieved in accordance with the profit target has been adjusted. And by using this method of target costing, companies can reduce the cost of production per unit of car